Becoming a successful manager : powerful tools for making a smooth transition to managing a team - Parkinson, J. Robert (John Robert) (McGraw-Hill, 2010)
Presenting numerous exercises throughout; this book aims to help you; as a new manager; quickly assimilate some of the basic knowledge you must have and actions you must put into practice in order to succeed. --